USING THE VAR MODEL TO INVESTIGATE SOME OF THE ECONOMIC DRIVERS OF TOURISM IN MONGOLIA - Da-Lai; Amarjargal.S (Journal of Business and Innovation (Бизнес & Инноваци), 2024)
This study uses VAR models to elucidate the ways in which economic factors from China, Russia, and South Korea impact Mongolia’s tourism demand. The VAR model, which uses impulse response analysis and variance decomposition to capture the dynamic temporal implications of economic indicators like GDP and exchange rates on visitor flows. The demand for travel in the Russian, South Korean, and Chinese markets is significantly correlated, and China’s significant contribution to Mongolia’s tourism industry is highlighted. The findings of our study indicate that risk management and regional cooperation might be among the expected outcomes. Additionally, this study offers data-driven policy recommendations meant to boost Mongolia’s tourist sector’s competitiveness internationally.